Amnistías e historia política: huellas y problemas en el siglo XX - Cossío Díaz, José Ramón; Rodríguez Kuri, Ariel (El Colegio de México, A.C., 2022)
This article proposes an analysis of four moments in which amnesty laws of a political nature were enacted in Mexico: January 1937, December 1940, September 1978 and January 1994. In each case, an attempt is made to analyze the subject and contents of the amnesty laws, along with their political context. We have not always been able to determine the beneficiaries as we have with their legal and political aspects. A detailed exploration of archives and official publications would allow one to uncover evidence of proposed amnesties not covered by this article. The underlying premise used herein is that amnesty laws are one key to understanding the political history of a large part of the 20th Century. By studying them, it is possible to more fully understand the judicial functioning of the Constitution of 1917.